Persistent Transmission of Citrus Vein Enation Virus by Aphis gossypii and Myzus persicae - Hermoso-De-Mendoza, Alfonso; Pina, José A.; Ballester-Olmos, José F.; Navarro, Luis (IOCV, 2021)
Citrus vein enation virus (CVEV) is widely distributed in Spain and circumstantial evidence suggests a high rate of natural spread. No experimental transmission was achievedin extensive trials with several aphid species using a 2-day acquisition period and a 2-day inoculation period. In further experiments, using a 5-7 day acquisition period and a 9-16 day inoculation period, a 95% transmission efficiency was obtained with Aphis gossypii and 10% with Myzus persicae. Furthermore, a 10% transmission efficiency was achieved with viruliferous A. gossypii maintained on healthy plants for a period of up to 14 days after acquisition then given an 11-day inoculation access feed. These results show that CVEV is persistently transmitted by A. gossypii in Spain, thus explaining the high rate of natural spread in the field.